PHOSPHATE FERTILIZATION AND SHADING ON THE INITIAL GROWTH AND PHOTOCHEMICAL EFFICIENCY OF Campomanesia xanthocarpa O. BERG. - Silvério, Juliana Milene; Espíndola, Giselly Marques; Santos, Cleberton Correia; Scalon, Silvana de Paula Quintão; Vieira, Maria do Carmo (Floresta, 2020)
Campomanesia xanthocarpa O. Berg. (“Gabirobeira”, Myrtaceae) is a versatile fruit tree species native in Cerrado. Studies of mineral fertilization and luminous conditions with the species are incipient. Thus, the aim was to evaluate the initial growth and photochemical aspects in C. xanthocarpa cultivated under phosphate fertilization and shading levels. The experiment was carried out in plastic pots and the factors under study consisted of five doses of phosphorus: 0, 50, 100, 150 and 200 mg kg soil-1, and two shadings levels: 0% (full sun) and 50%. The treatments were arranged in a 5 x 2 factorial scheme, in a randomized block design, with four replications. The greatest growth characteristics occurred at 240 days after transplantation. The highest chlorophyll index was seen in shaded leaves. The highest values of variable and maximum chlorophyll-a fluorescence were with 10.8 and 11.6 mg P kg-1 in shaded environments, and with 120.0 and 81.81 mg P kg-1, under full sun. The highest photochemical efficiency in photosystem II (Fv/Fm) was under full sun with 33.33 mg P kg-1. The analysis of main components explained 78.82% of the remaining variability. The shaded C. xanthocarpa plants showed higher photochemical yields with the addition of low phosphorus doses. Phosphate fertilization contributed to the mitigation of photochemical damage in young plants of C. xanthocarpa cultivated under full sun.